2018
DOI: 10.3390/ijms19020480
|View full text |Cite
|
Sign up to set email alerts
|

CircSMARCA5 Inhibits Migration of Glioblastoma Multiforme Cells by Regulating a Molecular Axis Involving Splicing Factors SRSF1/SRSF3/PTB

Abstract: Circular RNAs (circRNAs) have recently emerged as a new class of RNAs, highly enriched in the brain and very stable within cells, exosomes and body fluids. To analyze their involvement in glioblastoma multiforme (GBM) pathogenesis, we assayed the expression of twelve circRNAs, physiologically enriched in several regions of the brain, through real-time PCR in a cohort of fifty-six GBM patient biopsies and seven normal brain parenchymas. We focused on hsa_circ_0001445 (circSMARCA5): it was significantly downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
168
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(177 citation statements)
references
References 47 publications
6
168
0
1
Order By: Relevance
“…CircRNA is more diverse in neuronal tissue than other tissues and plays critical roles in brain diseases, such as cerebrovascular disease and neurodegenerative disease . Recently, evidences suggested that the key role of circRNAs in the molecule mechanism of glioma development, where some circRNA promote glioma malignancy and some circRNA inhibit glioma progression . It is still few evidences of the role of circZNF609 in glioma carcinogenesis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…CircRNA is more diverse in neuronal tissue than other tissues and plays critical roles in brain diseases, such as cerebrovascular disease and neurodegenerative disease . Recently, evidences suggested that the key role of circRNAs in the molecule mechanism of glioma development, where some circRNA promote glioma malignancy and some circRNA inhibit glioma progression . It is still few evidences of the role of circZNF609 in glioma carcinogenesis.…”
Section: Introductionmentioning
confidence: 75%
“…[3,4] Recently, evidences suggested that the key role of circRNAs in the molecule mechanism of glioma development, [5,6] where some circRNA promote glioma malignancy [7,8] and some circRNA inhibit glioma progression. [9] It is still few evidences of the role of circZNF609 in glioma carcinogenesis. As previous study, circZNF609 was indispensable for the growth of central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identifying the underlying mechanisms of glioma development and finding new therapeutic targets is an urgent issue. A growing body of evidence that circRNAs are involved in the development of glioma as an oncogene or tumor suppressor (Xie 2018;He et al 2018;Barbagallo et al 2018). It has been reported that circKIF4A expression is significantly increased in glioma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…According to the reports of Liu et al [21], the function of circRNAs was also versatile to function as microRNA (miRNA) sponges [5,13] and protein sponges [22,23]. For example, the circSMARCA5 [24] and circCFH [25] have been found to be expressed in a glioma-speci c pattern which may be used as the tumor biomarkers. CircNFIX [26] and circNT5E [27] have been found that they play oncogenic roles in glioma, whereas circFBXW7 and circSHPRH have been reported to function as the tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%